Correlation between serum factor VIII:C levels and deep vein thrombosis following gynecological surgery - Jiayi Liu (Taylor & Francis Group, 2021)
Deep vein thrombosis (DVT) is common in patients following gynecological surgery. Coagulation factor VIII (FVIII) is an important part of the human coagulation system, and FVIII:C is a component of FVIII with anticoagulant activity. 800 patients who underwent gynecological surgery were enrolled. General clinical data were harvested, and pre – and postoperative serum FVIII levels were determined. Lower-extremity ultrasound examination and/or postoperative pulmonary angiography were performed. Related data were analyzed statistically. DVT was the first manifestation of venous thromboembolism in all cases. There were a total of 46 cases, and the incidence of DVT was 5.8%. Progression to pulmonary embolism was confirmed in 16 cases, with an incidence of 2.0%. The independent risk factors for DVT after gynecological surgery were postoperative FVIII:C levels (odds ratio [OR] = 1.01), age (OR = 6.57), and operation time ≥3 hours (OR = 2.90) (P < 0.05). When the FVIII:C level was greater than the 75th centile (≥150 IU/dL), the risk of DVT was 2.99 times higher than that below the 25th centile (<100 IU/dL) (P < 0.05). When combined with the risk factor of operation time ≥3 hours, the risk increased to 3.17 times (P = 0.10). When combined with age ≥60 years, the risk was significantly increased, reaching 12.0 times (P < 0.05). Serum FVIII:C levels are an independent risk factor for DVT after gynecological surgery. Higher levels increase the risk of DVT after gynecological surgery, and they may have a dose-dependent relationship. A synergistic effect exists in combination with other risk factors, which further increases the risk.